Social entrepreneurship concepts, methodologies, tools, and applications (IGI Global, 2019)
"This book examines the broad topic of social entrepreneurship by looking at relevant theoretical frameworks and fundamental terms. It also addresses the challenges and solutions social entrepreneurs face as they address their corporate social responsibility in an effort to redefine the goals of today's enterprises and enhance the potential for growth and change in every community"--